(untitled) (Swiss Medical Weekly, 2013)
Since publication of the initial guidelines for the prevention of group B streptococcal disease in 1996, the incidence of perinatal infection has decreased significantly. Intrapartum antibiotic prophylaxis together with appropriate management of neonates at increased risk for early-onset sepsis not only reduces morbidity and mortality, but also decreases the burden of unnecessary or prolonged antibiotic therapy. This article provides healthcare workers in Switzerland with evidence-based and best-practice derived guidelines for the assessment and management of term and late preterm infants (>34 weeks) at increased risk for perinatal bacterial infection. Management of neonates at increased risk for early-onset sepsis depends on clinical presentation and risk factors. Asymptomatic infants with risk factors for early-onset sepsis should be observed closely in an inpatient setting for the first 48 hours of life. Symptomatic neonates must be treated promptly with intravenous antibiotics. As clinical and laboratory signs of neonatal infection are nonspecific, it is mandatory to reevaluate the need for continued antibiotic therapy after 48 hours.